Political legitimacy in a non-optimal currency area - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2013)
On the basis of a brief reconstruction of the causes and impacts of the euro crisis, this paper explores, counterfactually and hypothetically, whether the new euro regime, insisting on fiscal austerity and supply-side reforms, could have prevented the rise of the crisis or is able to deal with its disastrous economic and social impact. A comparison with the likely impact of transfer-based Keynesian reflation suggests that, in both cases, economic success is uncertain, while both approaches are likely to produce severely negative side-effects. In light of such dismal policy choices, attempts to politicize European election campaigns are more likely to provoke unmanageable policy conflict than to overcome the input-oriented, democratic deficit of European economic governance. – – Das Papier analysiert die Ursachen der Eurokrise und fragt dann, kontrafaktisch und hypothetisch, ob das neue, auf fiskalische Konsolidierung und strukturelle Reformen setzende Euro-Regime die Krise hätte vermeiden können oder jetzt geeignet wäre, deren desaströse ökonomische und soziale Folgen zu überwinden. Ein Vergleich mit der Alternative einer keynesianischen Politik der transfergestützten fiskalischen Reflation zeigt, dass in beiden Fällen der ökonomische Erfolg ungewiss bleibt, aber auf jeden Fall mit gravierenden negativen Nebenwirkungen zu rechnen ist. Angesichts derart unerfreulicher Politikoptionen würde der Versuch einer Politisierung der Wahlen zum Europäischen Parlament eher kaum zu bewältigende Richtungs- und Verteilungskonflikte provozieren, als zu einer Überwindung des europäischen Demokratiedefizits beitragen.
Keywords: 300